Prevalencia de anaplasmosis en bovinos en el cantón Santa Rosa - Ruiz Lozano, Kleber Jorlyn (2011)
This research was conducted during November 2009 to October 2010 on Santa Rosa, province of El Oro Santa Rosa is located in the western coastal plain of Ecuador Central in the province of El Oro, and is divided into 9 parishes. O has an altitude of 500 meters, an average temperature of 26 ° C-29 ° C, and an area of 88,850 hectares. To make this work were taken blood 350muestras beef cattle and milk, they were chosen at random. Was used as a diagnostic method of Giemsa staining, by puncture with a lancet in the ear to some animals and others, in the capillary flow. Once the sample, a smear of fine droplets on a slide and took it to the laboratory where they were fixed with methanol and stained with Giemsa to then take the reading. The rickettsia was identified microscopically within red blood cells, showing a round or punctate, the color pink, reaching toward the center of the erythrocyte, in the case of Anaplasma ççntrale and towards the periphery, to Anaplasma marginale.